2017
DOI: 10.1038/pr.2017.274
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived fatigue in adolescents in relation to body composition and physical outcomes

Abstract: BackgroundIncreased self-perceived fatigue (SpF) has already been identified in chronic conditions such as obesity, but it is also a growing problem in school-attending adolescents (±25%). This study tried to link body composition to SpF and physical activity/performance. Additionally, indicators for fatigue were determined.MethodsA total of 452 adolescents were recruited. Body composition was measured and physical activity, physical performance, and SpF were assessed. Based on the total SpF (Multidimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Fatigue is a symptom frequently complained of by obese patients, particularly those with a long duration of the disease or with advanced age [17,18,30]. Fatigue represents one of the most important reasons for failure, non-adherence or drop-out in any exercise-based BWRP in a pediatric obese population [31,32]. In the present study, FSS score decreased at the end of the BWRP in all subgroups of obese subjects (females/males and with/without metabolic syndrome), both confirming and extending the results of one of our previous studies, in which severely obese adults (age: 18-83 years and BMI: 35.0-65.3 kg/m 2 ) underwent a similar intervention [19].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is a symptom frequently complained of by obese patients, particularly those with a long duration of the disease or with advanced age [17,18,30]. Fatigue represents one of the most important reasons for failure, non-adherence or drop-out in any exercise-based BWRP in a pediatric obese population [31,32]. In the present study, FSS score decreased at the end of the BWRP in all subgroups of obese subjects (females/males and with/without metabolic syndrome), both confirming and extending the results of one of our previous studies, in which severely obese adults (age: 18-83 years and BMI: 35.0-65.3 kg/m 2 ) underwent a similar intervention [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although the anthropometric characteristics and lifestyle habits in childhood suggest that it is closely related to physical fitness, it is stated that other parameters may indirectly affect lifestyle habits (Arnaoutis et al, 2018). In order to determine the health status of children and adolescents, the importance of using fat mass and fat percentage which are evaluated by bioelectrical impedance analysis instead of BMI are emphasized (Vantieghem et al, 2018). Therefore, anthropometric parameters (Pavlovic et al, 2018) such as body weight, lean body mass, fat mass and muscle mass are very closely related to health development in adolescence (Lopes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anthropometric parameters (Pavlovic et al, 2018) such as body weight, lean body mass, fat mass and muscle mass are very closely related to health development in adolescence (Lopes et al, 2018). Because body composition parameters related to physical health should be well defined, and being physically active is one of the healthiest behaviors (Vantieghem et al, 2018). Therefore, adolescents are advised to perform moderate to vigorous physical activity for at least 60 minutes per day (WHO, 2010a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It ensures maintenance of the balance with the information collected from these structures [ 32 , 34 ]. The proprioceptive system is affected by fatigue, aging, sarcopenia, neurological disease fibromyalgia, cancer, and rheumatological diseases and may result in impaired balance [ 35 , 36 , 37 , 38 ]. Many researchers have shown that fatigue negatively affects dynamic postural control [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%